2000
DOI: 10.2525/jshita.12.83
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedback Guidance of Manipulator for Eggplant Harvesting using Fuzzy Logic.

Abstract: This study was conducted as a first step in the development of the robotic harvesting system for eggplants.The robotic harvesting system with hand-eye structure was fabricated and the visual feedback fuzzy control model to operate the manipulator was developed.The control model was examined in terms of manipulator guidance to the fruit, estimation of the fruit maximal diameter for selective harvesting and estimation of the fruit angle for the picking movement.From the results of the approach experiment, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…It was confirmed that the algorithm could be used under different light conditions, although the algorithm detected a part of the fruit in the case of direct sunlight conditions. Manipulator guidance to fruit by fuzzy logic 4 After detection of the fruit by the machine vision unit, the manipulator approached the fruit with the use of machine vision data. A fuzzy logic was adopted for the manipulator guidance, since the machine vision algorithm would not always detect the whole part of fruit.…”
Section: System Componentsmentioning
confidence: 99%
“…It was confirmed that the algorithm could be used under different light conditions, although the algorithm detected a part of the fruit in the case of direct sunlight conditions. Manipulator guidance to fruit by fuzzy logic 4 After detection of the fruit by the machine vision unit, the manipulator approached the fruit with the use of machine vision data. A fuzzy logic was adopted for the manipulator guidance, since the machine vision algorithm would not always detect the whole part of fruit.…”
Section: System Componentsmentioning
confidence: 99%